Recurrent painful angioleiomyoma of the hindfoot: a case report - Souza Júnior, Eli Ávila; Pinto, Roberto Zambelli de Almeida; Lopes, Fernando Araújo Silva (Scientific Journal of the Foot & Ankle, 2019)
Foot angioleiomyomas are rare tumors that are more prevalent in older women, may be asymptomatic, and rarely recur after surgical excision. We report an atypical case in a young woman of a painful and recurrent angioleiomyoma after excision. Level of Evidence V; Diagnostic Studies; Expert Opinion.